Soft tissue infection caused by Burkholderia cepacia in a child with polyarteritis nodosa - Yıldız, Başak; Duyu, Muhterem; Sözeri, Betül; Karapınar, Bülent (The Turkish Journal of Pediatrics, 2012)
Burkholderia cepacia belongs to a family of Burkholderia species previously described as Pseudomonas cepacia, especially in patients suffering from cystic fibrosis. There are also many studies about this agent in the last decade due to their life-threatening infections and ability to invade mucosal and cellular surfaces. Here, we report a case of soft tissue infection caused by B. cepacia in a child with an underlying condition of polyarteritis nodosa. Her complaints started at two months of age and she was on cyclosporine therapy. She was treated several times because of soft tissue infections especially in her extremities. The most common causative agents were Pseudomonas spp. and Escherichia coli, but recently, another soft tissue infection accompanied by fever and signs of sepsis had developed. All blood, urine and tissue (debrided from the necrotic area) specimens were incubated. Empirical antibiotherapy with clindamycin was started and cyclosporine therapy was discontinued. B. cepacia was grown in the tissue specimen culture and was only susceptible to carbapenems. Meropenem therapy was administered throughout 14 days with a daily dosage of 60 mg/kg, and she was treated successfully at least in this attack of soft tissue infection, which caused more severe sepsis and tissue damage than the previous infections with other agents.